Citizen Journalism Training to Strengthen the Role of Youth in Overseeing the Village Development - Rahmad Hidayat; Tauhid Tauhid; Muhammad Sauki (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
This training focuses on testing the effectiveness of citizen journalism as a variant of social engineering for the realization of social accountability in managing village development. The potential and active participation of the youth in overseeing the management of village development needs to be sharpened or strengthened through training in the use of media and communication tools. The role of youth must be maximized in a more positive direction in the framework of village policy so they can contribute significantly to improve the pattern of village development management which will significantly influence the acceleration of public welfare achievement. Citizen journalism as a special variant of social engineering must be tested for its relevance and be further developed as an instrument for the realization of social accountability in the village that requires the community to play the role of supervisor for all village government actions. It is conducted by publishing photo-voice narratives in various available communication channels in the village, both in printed and electronic forms. This activity has been carried out for four months in 2019 (August-November) through two learning phases which are classroom learning and mentoring for transferring basic knowledge and reviewing everything that intersects with prospects, constraints and substantive needs of this citizen journalism intervention. Methods used in the training included lectures, discussions, photo-film displays, simulation, presentations, and mentoring. This intervention was effective to increase the youth’s knowledge and skill about producing various items of citizen journalism to disseminate substantive information to the public as well as to forge their courage to have a direct dialogue with the village government apparatus regarding important issues that have not been included in the formulation of village development programs.